ChemInform Abstract: Mild Palladium‐Catalyzed Regioselective Direct Arylation of Azoles Promoted by Tetrabutylammonium Acetate. Issue 6 (11th February 2014) - Bellina, Fabio; Lessi, Marco; Manzini, Chiara
Abstract A simple and efficient method to prepare several 5‐arylated azoles is presented.